Datasets for "The causal-noncausal alternation in the Northern Tungusic languages of Russia". - Aralova, Natalia; Pakendorf, Brigitte (Zenodo, 2020)
These are the datasets used in the paper Aralova, N. & B. Pakendorf (to appear): The causal-noncausal alternation in the Northern Tungusic languages of Russia . Special issue of Linguistic Discovery on "The Tungusic language family through the ages" edited by A. Hölzl and Tom Payne. For more details, see the ReadMe file. Please contact the authors if you want to use these datasets before the paper is published. : We thank Galina I. Kandakova and Antonina V. Kazarova for their help in compiling the Negidal dataset. We would like to acknowledge the Endangered Languages Documentation Programme (ELDP), www.eldp.net, for generously funding our work on Negidal. We also thank the LABEX ASLAN (ANR-10-LABX-0081) of Université de Lyon for its financial support within the program "Investissements d'Avenir" (ANR-11-IDEX-0007) of the French government operated by the National Research Agency (ANR). Furthermore, Natalia Aralova would like to acknowledge that her work was supported by the subsidy of the Russian Government to support the Program of Competitive Growth of Kazan Federal University.